English as a Lingua Franca in Spontaneous Online Communication: Learners’ Experiences through Ome TV - Fadilah Nur Fauzi; Tauricha Astiyandha; Ellis Tamela (Universitas Pahlawan Tuanku Tambusai, 2026)
English increasingly functions as a global medium for interaction, particularly in online environments where speakers come from diverse linguistic backgrounds and do not share the same first language. From the perspective of English as a Lingua Franca (ELF), the focus is placed on intelligibility, mutual understanding, and effectiveness rather than native-like accuracy. On platforms such as Ome TV, English often becomes the shared language that enables users from different countries to interact in real time. This study aims to explore learners’ experiences and strategies when using ELF in spontaneous digital interaction. The study employed a descriptive qualitative design within an interpretive ELF framework. Data were collected through semi-structured interviews with ten participants who frequently interacted with international users on Ome TV and were analyzed using thematic analysis. The findings reveal that English functions as a practical shared language that facilitates cross-cultural exchange in informal digital settings. Participants used strategies such as paraphrasing, simplifying expressions, repetition, and occasional code-switching to maintain interaction and overcome linguistic limitations. These findings highlight the role of spontaneous online platforms in supporting communicative competence and strategic language use.